Pengembangan Sistem Toko Online Alat Kesehatan berbasis Mobile dengan menggunakan Framework Angular (Studi Kasus: Yes Medika) - Aulia Muhammad Hariz; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
E-comerce is a new paradiggm in the bussiness world that change the traditional trade paradiggm, from conventional trading to electronic comerce commerce by utilizing Information and Communication Technology (ICT) or better known as internet technology (Karimi, 2020). Humans are starting to feel comfortable using e-commerce systems, because by shopping online humans no longer have to go to shopping centers (Prajok, 2021). Through the e-commerce system, users only need to visit the e-commerce site, shop for what they need, the payment is completed, and the product arrives at the doorstep according to the delivery time. The use of e-commerce can be accessed via a computer, laptop, tablet, or smartphone. Considering nowadays it can be said that almost everyone uses gadgets, from computers, laptops, tablets, or smartphones, this certainly make it easy for customer for transactions online.